Anatomy of b → c τ ν anomalies - Aleksandr Azatov; Debjyoti Bardhan; Diptimoy Ghosh; Francesco Sgarlata; Elena Venturini (Journal of High Energy Physics, 2018)
Abstract In recent times, one of the strongest hints of Physics Beyond the Standard Model (BSM) has been the anomaly in the ratios R D and R D * $$ R_{D^{*}} $$ measured in the charged current decays of B-mesons. In this work, we perform a comprehensive analysis of these decay modes, first in a model independent way and subsequently, in the context of composite Higgs models. We discuss in depth as to how linearly realised SU(2)L × U(1)Y symmetry imposes severe constraint on the various scenarios because of correlations with other ΔF = 1 processes and Z τ τ and Z ν ν couplings. In the composite Higgs paradigm with partial compositeness, we show that, irrespective of the flavour structure of the composite sector, constraints from ΔF = 2 processes bring the compositeness scale down to ∼ 650 GeV which is in tension with electroweak precision observables. In the presence of composite leptoquarks, the situation improves only marginally (a factor of 2 $$ \sqrt{2} $$ in the compositeness scale), thus making the new states soon discoverable by direct searches at the LHC. We also comment on the possible explanation of the R K , K * $$ R_{K,K^{*}} $$ anomalies within the composite Higgs framework.